PELATIHAN PENULISAN ARTIKEL ILMIAH UNTUK MENDUKUNG KOMPETENSI PROFESIONAL GURU - Sofwan, Muhammad; Habibi, Akhmad; Destrinelli, Destrinelli; Hayati, Suci (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Limited knowledge of teachers in the process of writing scientific articles as a means of this service. Based on the results of interviews at the KKG for Elementary School Teachers in Pamenang with the chairman of the KKG, information was obtained that: there are still teachers who have difficulty using scientific article writing. This occurs because there is a lack of concise training assistance for the process of writing scientific articles. On average, the reason is a lack of understanding of the guidelines for writing scientific papers and teachers are not used to using the media as a reference source, then there are no training activities organized by the KKG to increase teachers' knowledge in writing scientific articles. Seeing the problems that exist in the KKG Teacher Team in Pamenang regarding the problem of writing scientific articles, it is necessary to carry out a Journal Article Writing Training to Support Professional Competence for the KKG Teacher Team in Pamenang. The objectives to be achieved through this training activity are: 1). The production of scientific articles by teachers which can later be used as material for promotion. 2). Produced articles published in online media, 3) Produce Scientific Articles which will be published in the PPM Journal. 4). Affirm Activities.